Relationship Between the Level of Knowledge and Medication Adherence Level in Diabetes Mellitus Patients in Advent Medan Hospital - Amazihono, Keytrin; Erida Novriani; Lubis, Asyrun Alkhairi (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
Hyperglycemia or elevated blood sugar levels due to decreased pancreatic insulin productin, is a sign of a metabolic disorder that leads to diabetes mellitus (DM). One crucial factor in managing diabetes mellitus is the patient’s knowledge and adherence to treatment. Patients with adequate knowledge are more likely to comply with therapy, which helps control the disease. This study aims to determine the relationship between the level of knowledge and the level of medication adherence in diabetes mellitus patients in Advent Hospital Medan. This research employed a quantitative approach with a cross-sectional design and a purposive sampling technique. The research involved 90 patients who were selected and agreed to participate as respondents. Data were collected using a validated Diabetes Knowledge Questionnaire (DKQ-24) and Medication Adherence Report Scale (MARS-5). Data analysis was conducted using a non-parametric statistical test, specifically the Chi-Square test. The study found that the majority of patients had a high level of knowledge (48,9%) but were non-adherent to medication (56,7%). The Chi-Square test showed a significance of 0.001 < 0.05, indicating a significant relationship between the level of knowledge and medication adherence among diabetes mellitus patients at Advent Medan Hospital.